Pelatihan Keterampilan Asertif Berbasis Interactive Learning sebagai Upaya Penguatan Mental dan Emosional Bagi Siswa Sekolah Dasar dalam Melawan Perilaku bullying - Anastasia Wulandari,; Eka Fauziyya Zulnida,; Siti Chotidjah,; Muhammad Ariez Musthofa,; Syahnur Rahman, (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Cases of bullying or bullying in Indonesia claim many lives. The distribution of the 30 bullying cases included middle school (50%), elementary school (30%), high school (10%), and vocational school (10%). Of these 30 cases of bullying, there were cases that claimed lives, namely one elementary school student in Sukabumi Regency and one MTs student in Blitar (East Java). Both died after experiencing violence from peers within the educational unit (Rosa, 2023). The increasing number of reports of bullying against children is a serious concern for the Psychology Study Program at the Indonesian University of Education (UPI). This is in line with one of the study program's missions, namely realizing community welfare. Children's welfare is an integral part of society's welfare which can be measured through various indicators, including those regulated in Law Number 35 of 2014 concerning Child Protection. This law emphasizes that every child, including young children, has the right to grow and develop optimally. These rights must be guaranteed, protected and fulfilled by parents, family, society and the state. Unfortunately, aggressive behavior such as violence and bullying among children can have long-term impacts, including increased risk of psychological disorders, poor social functioning, and obstacles in the educational process. As an institution committed to the welfare of society, the UPI Psychology Study Program has an important role in providing education, intervention and research that supports efforts to prevent and handle bullying and violence against children. Based on the presentation of this case, the Psychology Study Program at the Indonesian Education University felt the need to carry out preventive efforts in the form of assertive communication training to minimize the increase in bullying behavior. The aim of this training is to provide training to elementary school teachers so they can train their students about the importance of assertive behavior and develop assertive behavior in an effort to prevent bullying behavior. The method used in this community service was providing material regarding assertive communication. The number of training participants was 116 people who were elementary school teachers spread across the Sukabumi Regency area. There is a pre-test and post-test to test the teachers' knowledge. The results of the analysis show that there is a significant increase in knowledge and the training participants gave a positive response in terms of teaching and implementation.